Dampak Return On Asset (ROA),Current Rasio Dan Debt to Equity Ratio (DER) Terhadap Total AssetTurnoverm Pada Perusahaan Manufaktur Di BEI - Hariatih, Hariatih; Kartini, Kartini; Sundari, Sri (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on Total Asset Turnover (TATO) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The background of this research is the phenomenon of asset utilization inefficiency, as indicated by stagnant or declining TATO values despite increasing asset levels. This research employs an associative quantitative approach using secondary data from annual financial reports of manufacturing companies. Data analysis was conducted using multiple linear regression with the assistance of SPSS software.The results show that ROA and DER have a positive and significant effect on TATO, while CR does not have a significant effect. These findings indicate that companies capable of generating profits from their assets and having an efficient debt-based capital structure tend to achieve higher asset utilization efficiency. Conversely, excessive liquidity does not always contribute positively to asset efficiency.